Faktor-Faktor yang Memengaruhi Munculnya Tanda Gejala Depresi di Masa Pandemi Covid-19 - Putu Ayu Emmy Savitri Karin; Ni Komang Semara Yanti; Ni Nyoman Clara Listya Dewi (Jurnal Ilmu Keperawatan Jiwa, 2021)
COVID-19 pandemic not only has significant impact on public health but also on public mental health. It is shown by the increasing number of people with depression during this pandemic. Studies reveal that there are several factors can predict depressive symptoms during COVID-19 pandemic. This study aimed to identify factors that significantly predict depressive symptoms during COVID-19 pandemic. In the present literature review, articles that focused on factors predicting depressive symptoms among general population during the COVID-19 pandemic were searched in the ProQuest, PubMed and Google Scholar databases by using Boolean Operator. Words such as general population, adult, predicting factors, protective factors, risk factors, depressive symptoms, depression, during pandemic COVID-19 were used as keywords. Then, 114.823 potential studies were found and screened based on inclusion criteria. The final 14 articles were reviewed and used in this study. The majority of population in the present study aged 18 years old and older with the total population was 129.527. Age, gender, marital status, having children, employment status, history of having mental illness, education, income and loneliness are factors that significantly predict depressive symptoms among general population during COVID-19 pandemic. These social determinants and loneliness were found as predictive factors of depressive symptoms among general population during COVID-19 pandemic.